x+0.08(60)=0.20(60+x)

Simple and best practice solution for x+0.08(60)=0.20(60+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+0.08(60)=0.20(60+x) equation:


Simplifying
x + 0.08(60) = 0.20(60 + x)

Multiply 0.08 * 60
x + 4.8 = 0.20(60 + x)

Reorder the terms:
4.8 + x = 0.20(60 + x)
4.8 + x = (60 * 0.20 + x * 0.20)
4.8 + x = (12 + 0.20x)

Solving
4.8 + x = 12 + 0.20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.20x' to each side of the equation.
4.8 + x + -0.20x = 12 + 0.20x + -0.20x

Combine like terms: x + -0.20x = 0.8x
4.8 + 0.8x = 12 + 0.20x + -0.20x

Combine like terms: 0.20x + -0.20x = 0.00
4.8 + 0.8x = 12 + 0.00
4.8 + 0.8x = 12

Add '-4.8' to each side of the equation.
4.8 + -4.8 + 0.8x = 12 + -4.8

Combine like terms: 4.8 + -4.8 = 0.0
0.0 + 0.8x = 12 + -4.8
0.8x = 12 + -4.8

Combine like terms: 12 + -4.8 = 7.2
0.8x = 7.2

Divide each side by '0.8'.
x = 9

Simplifying
x = 9

See similar equations:

| y-3.4=8 | | 5y+10-3y-y=-7 | | 7(x-5.1)=5.6 | | 8b+3b=b | | 2x^4-9x^3-4x^2=0 | | 8x+9.84=4x+14 | | 2w+8w+w=329 | | 5x-3x+5=x+8 | | x^2+2x-33=0 | | 11h-5h+16=4 | | 6.9m+1.96=-49.79 | | 0.2x+0.4=3.6 | | 7.7x=-60.06 | | x-4=7.26 | | 10-6x-4+8x=12 | | 0=35-5x-2x | | -5y=4.95 | | p(4b-1)=2(9b+3) | | x+3.1=7.3 | | 14s^2-167st-12t^2=0 | | x^2+5x+31= | | 0=7m+4-3m | | x+10=-30 | | (x+5)(3x-9)=0 | | s=2*3.14*r^2+2*3.14*r*h | | 2(2t-3)=6(t-2) | | 57x+4334635x-30409234809x=28934237409x+23423423x*12312321x | | 7t-8=2+5t | | -2+p+2p+2=-12 | | 5m-12=-10+4m | | -36-b-4b=64 | | 5m+1=-23 |

Equations solver categories